ANALYSIS STUDENTS INTEREST IN AN INTEGRATIVE CONTEXT: A DESCRIPTIVE AND COMPARATIVE STUDY IN CHEMISTRY LEARNING - Anzalina, Hofifah; Pranata, Ogi Danika; Ramadani , Ramadani (JPPIPA (Jurnal Penelitian Pendidikan IPA), 2024)
Understanding students’ interest in learning chemistry is essential for educators to design effective teaching strategies and promote academic success. This study aims to investigates the learning interest in chemistry among students at different grade levels in SMAN 7 Kerinci, focusing on the integration of mathematics with chemistry lessons. Through descriptive and comparative analyses, we examine the factors influencing students’ interest in chemistry and its integrative context with mathematics. Our findings reveal that students’ interest in learning chemistry tends to decline as they progress through higher grade levels, with 11th grade students showing a higher interest compared to 12th grade students. Additionally, the integration of mathematics with chemistry poses challenges for students, impacting their interest levels. This study underscores the importance of innovative teaching approaches to enhance students’ interest and engagement in chemistry education. Further research is needed to explore the underlying factors influencing students’ interest in learning chemistry comprehensively. By understanding these factors, educators can develop targeted interventions to foster students’ interest and passion for chemistry, ultimately promoting academic success and nurturing future scientists and innovators.